Menthol mouth rinsing improves cycling performance in females under heat ttress - Gavel, E. G. (2019)
This study investigated the effects of a menthol mouth rinse on performance and physiological responses in female cycling athletes during a 30-km individual time trial (ITT). Participants(n=9) cycled for 30-km in hot conditions (30 ± 0.6 °C, 70 ± 1% relative humidity, 12 ± 1 km/h windspeed) on two test occasionsusing a menthol (MEN) mouth rinse (MR) occurring every 5 km. Perceptual responses (perceived exertion and thermal perception) were recorded at 5, 10, 15, 20, 25, and 30-km. The MEN MR significantly improved ITT performance by 2.3 ± 2.7% relative to PLA (p= 0.034, d= 0.85, 95% CI= 8.43 to 166.9). There were no significant differences in perceived exertion and thermal perception.These results demonstrate that a non-thermal cooling agent can improve physiological performancein moderately trained female cyclists with nochange in perceived exertion or thermal perception.